Representation Of #Wargabantuwarga Digital Activism During The 2025 Sumatra Flood Crisis: A Critical Discourse Analysis Study - Bagus Santoso; Fakhrur Rozi (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2026)
This study analyses the representation of digital activism in Ferry Irwandi’s #WargaBantuWarga campaign on Instagram by applying Ruth Wodak’s Critical Discourse Analysis, particularly the Discourse-Historical Approach, to examine the relationship among text, historical context, power relations, and intertextuality. The study employs a qualitative method using posts, captions, comments, follow-up podcasts, and cross-platform digital conversations related to the hashtag, supported by sentiment and emotion tracing. The analysis covers the identification of social problems, contextual analysis, discursive and linguistic strategies, and critical interpretation, with validity strengthened through expert triangulation. The findings show that Ferry Irwandi’s two videos function not only as representations of humanitarian assistance, but also as sites for the production of moral legitimacy, citizen solidarity, criticism of institutional responses, and the shifting of public trust from the state to citizen networks. This study contributes to disaster communication research by showing that digital activism should be understood not merely as aid communication, but as a discursive arena in which solidarity, legitimacy, and social authority are actively negotiated.fe.